A Broadband Compatible Multispectral Metamaterial Absorber for Visible, Near‐Infrared, and Microwave Bands. Issue 9 (5th March 2018) - Li, Meiling; Muneer, Badar; Yi, Zixuan; Zhu, Qi
Abstract: A design of a compatible multispectral metamaterial absorber with broadband and strong absorption in the microwave, visible‐light, and near‐infrared bands is presented based on conductive carbon black (CCB)‐filled polyethylene (PE) composite films. The CCB‐filled PE composite films are employed to not only attenuate the light energy for realizing visible and near‐infrared absorbers, but also provide a conductive film to construct resistive metamaterial surfaces for realizing a microwave absorber. Considering the two natural properties of the composite films, light attenuation property and electric property, a multilayered structure based on resistive metamaterial surfaces is designed to realize a broadband compatible absorber. These resistive metamaterial surface layers are realized by the prepared composite films. The effect of different resistances of resistive metamaterial surfaces, polarization, and incident angles on the microwave absorbing performance is also analyzed in detail. Finally, a compatible multispectral absorber with a total thickness of 17 mm (0.133λmax ) is fabricated and measured. Simulated and measured results both show that the presented absorber can achieve an absorption of 96.8% over a frequency range from 2.35 to 18 GHz. On the other hand, a high absorption of about 95% is obtained in visible‐light and near‐infrared bands as well. Abstract : The natural properties of conductive carbon black filled polyethylene composite film, i.e. light attenuation property and electric property, are utilized to develop a compatible multispectral absorber. The thin absorber achieves an absorption efficiency of more than 95% in the microwave (2.35–18 GHz), visible, and near‐infrared bands. The design method and analytical principle are also provided.